2020
DOI: 10.4178/epih.e2020074
|View full text |Cite
|
Sign up to set email alerts
|

The copro-molecular diagnosis of Sub-family Toxoplasmatinae in dog and cat population in northern Iran

Abstract: OBJECTIVES The oocysts of the Toxoplasmatinae subfamily ( Neospora caninum , Hammondia hammondi and H. heydorni , and Besnoitia besnoiti ) are morphologically similar to Toxoplasma gondii , and indistinguishable from each other. This study investigated the prevalence of the Toxoplasmatinae subfamily in dog and cat fecal samples using a nested polymerase chain react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Genera of the Toxoplasmatinae subfamily i.e., Toxoplasma , Besnoitia , and Hammondia , share oocyst morphology (<16 μm in diameter) and cannot be morphologically differentiated. These organisms as well as the coccidian Sarcocystis , have an indirect life cycle, and felids get infected by consuming intermediate hosts that carry the parasitic cysts in their tissues [ 49 , 50 ]. Various species of mammals are intermediate hosts of all four genera, including prey of wildcats and livestock.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genera of the Toxoplasmatinae subfamily i.e., Toxoplasma , Besnoitia , and Hammondia , share oocyst morphology (<16 μm in diameter) and cannot be morphologically differentiated. These organisms as well as the coccidian Sarcocystis , have an indirect life cycle, and felids get infected by consuming intermediate hosts that carry the parasitic cysts in their tissues [ 49 , 50 ]. Various species of mammals are intermediate hosts of all four genera, including prey of wildcats and livestock.…”
Section: Discussionmentioning
confidence: 99%
“…Various species of mammals are intermediate hosts of all four genera, including prey of wildcats and livestock. Felids are definitive hosts of Toxoplasma gondii , a parasite of great relevance in animal and human medicine, causing severe disease in immunocompromised individuals and abortions [ 50 , 51 ]. However, the whole range of species of Besnoitia , Hammondia , and Sarcocystis having felids as definitive host is yet to be determined [ 49 , 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Oocysts can be difficult to differentiate from those of Hammondia hammondi and Besnoitia spp. [49][50][51]; therefore, identification should be confirmed through molecular analysis. In the present study, the positive fecal sample in a wildcat was confirmed through molecular analysis.…”
Section: Discussionmentioning
confidence: 99%